Birth weight and adolescent blood pressure measured at age 12 years in the Gateshead Millennium Study. (9th December 2019) - Mann, K. D.; Basterfield, L.; Wright, C.; Parkinson, K.; Reilly, J. K.; Reilly, J. J.; Adamson, A. J.; Pearce, M. S.; ,
Abstract: Birth weight and early growth have been associated with later blood pressure. However, not all studies consistently find a significant reduction in blood pressure with an increase in birth weight. In addition, the relative importance of birth weight and of other lifestyle and environmental factors is often overlooked and the association is rarely studied in adolescents. We investigated early life predictors, including birth weight, of adolescent blood pressure in the Gateshead Millennium Study (GMS). The GMS is a cohort of 1029 individuals born in 1999–2000 in Gateshead in Northern England. Throughout infancy and early childhood, detailed information were collected, including birth weight and measures of height and weight. Assessments of 491 returning participants at age 12 years included measures of body mass and blood pressure. Linear regression and path analysis were used to determine predictors and their relative importance on blood pressure. Birth weight was not directly associated with blood pressure at the age of 12. However, after adjustment for contemporaneous body mass index (BMI), an inverse association of standardized birth weight on systolic blood pressure was significant. The relative importance of birth weight on later systolic blood pressure was smaller than other contemporaneous body measures (height and BMI). There was no independent association of birth weight on blood pressure seen in this adolescent population. Contemporaneous body measures have an important role to play. Lifestyle factors that influence body mass or size, such as diet and physical activity, where interventions are directed at early prevention of hypertension should be targeted.